Building Quality of Human Resources Through Job Skill Based on Local Wisdom of "Pageh, Puguh, Lan Jengah" at Village Credit Institutions (LPD) of Buleleng Regency - Ningsih, Luh Kartika; Prastiwi, Ni Luh Putu Eka Yudi (Journal of Business on Hospitality and Tourism, 2020)
The purpose of the research was to determine how to build quality of human resources through job skill based on “Pageh, Puguh, lan Jengah” at the Village Credit Institute (LPD) in Buleleng Regency. Through testing several relationships to determine the improvement in the quality of human resources in the LPD.This research used a quantitative approach. The data analysis technique used was Structural Equation Modeling-SEM) variance-based or component based SEM, called Partial Least Square (PLS) Visual version 3.0. The sample used 60 people with a t-table value for a significant level of α=0.05 of 1.96. All of the relationships showed positive and significant results. From the results of this research it is known that through the implementation of job skill based on “Pageh, Puguh, lan Jengah” is able to improve the quality of human resources that impacts on improving the performance of the employee in LPD of Buleleng Regency.